2017
DOI: 10.2136/vzj2016.07.0064
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Binding to Nanoparticles and Colloids in Forest Stream Waters

Abstract: Core Ideas• There are three distinct fractions of natural nanoparticles and colloids. • These unique fractions have different preferential P binding. • The fractions include Fe-P, organic C-P, and clay-P. • Field flow fractionation coupled online to OC detector for size resolved OC detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…We observed a negative correlation between the TC and TN content and P coll /TDP in aggregates, indicating that higher the TC and TN content, the less likely release of P coll from the soil aggregates, which was further confirmed by the negative correlation between TC and P coll /TDP in the regression model (Table 4). Studies had shown that C and N are important carriers of P coll (most organics act as organic colloidal complexes) [28,69,70], and the organic matter could stabilize Al/Fe colloids [71]. Therefore, increasing the carbon content in soil aggregates could be an important strategy to reduce the migration of P coll in the soil.…”
Section: Loss Potential Of Colloidal P In Aggregatesmentioning
confidence: 99%
“…We observed a negative correlation between the TC and TN content and P coll /TDP in aggregates, indicating that higher the TC and TN content, the less likely release of P coll from the soil aggregates, which was further confirmed by the negative correlation between TC and P coll /TDP in the regression model (Table 4). Studies had shown that C and N are important carriers of P coll (most organics act as organic colloidal complexes) [28,69,70], and the organic matter could stabilize Al/Fe colloids [71]. Therefore, increasing the carbon content in soil aggregates could be an important strategy to reduce the migration of P coll in the soil.…”
Section: Loss Potential Of Colloidal P In Aggregatesmentioning
confidence: 99%
“…Locating and apportionment of the sources and fluxes of the dissolved vs. collodial P conveyed by rivers in landscapes remains a longstanding and fundamental challenge for catchment scientists (see McClain et al, 2003;Bol et al, 2016;Gottselig et al, 2017b;Missong et al, 2018), with major implications for land management and nutrient pollution mitigation strategies. Colloidal P is characterized as dissolved P in most routine water quality monitoring programs (Gottselig et al, 2017a), however, it is believed to have reduced bioavailability compared to the truly dissolved P (Baken et al, 2014). Furthermore, colloids which consist of organic matter, Fe/Al oxyhydroxides and clay minerals (Jiang et al, 2015a;Missong et al, 2017) are important P carriers in and to surface waters (Gottselig et al, 2014(Gottselig et al, , 2017a and thus should be more explicitly accounted for in P budgets.…”
Section: Difficulties In Predictions Of Dissolved/colloidal/particulamentioning
confidence: 99%
“…The specific reactivity of nanoparticles is high, in comparison to larger‐sized colloids, (Hartland et al, ; Qafoku, ) rendering them potentially predominant carriers of nutrients in ecosystems. It has already been shown that NNP can bind the majority of P present in soil solutions (Hens & Merckx, ) and stream waters (Gottselig et al, , ) and that they can even support plant uptake of P from solution (Montalvo wt al., ). First results indicate that organic matter, Fe, and/or Al may be major binding partners for P in NNP of an acidic forest river system and that the binding of P varies depending on the stream water composition (Baken, Regelink et al, ; Gottselig et al, ).…”
Section: Introductionmentioning
confidence: 99%